2014
DOI: 10.1227/neu.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Estrogen in the Formation of Intracranial Aneurysms in Ovariectomized Female Mice

Abstract: Background Epidemiological studies have indicated that post-menopausal women have a higher incidence of intracranial aneurysms than men in the same age group. Objective We sought to investigate whether estrogen or estrogen receptors (ERs) mediate protective effects against the formation of intracranial aneurysms. Methods Intracranial aneurysms were induced in mice by combining a single injection of elastase into the cerebrospinal fluid with deoxycorticosterone acetate salt hypertension. The mice were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 33 publications
1
54
1
Order By: Relevance
“…Previous studies have shown that estrogen‐deficient rodents produce more aneurysms and that estrogen supplementation reverses this effect 5, 6, 7, 8. These previous studies do not corroborate what we observe clinically.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that estrogen‐deficient rodents produce more aneurysms and that estrogen supplementation reverses this effect 5, 6, 7, 8. These previous studies do not corroborate what we observe clinically.…”
Section: Discussioncontrasting
confidence: 99%
“…Approximately 70% to 75% of aneurysms occur in women,2 with postmenopausal women having the highest risk for aneurysm rupture 3, 4. Several studies have investigated estrogen deficiency and CA5, 6, 7, 8; however, the mechanism remains unknown. Understanding the mechanisms of aneurysms, particularly estrogen signaling, is needed to identify novel therapeutic targets.…”
mentioning
confidence: 99%
“…Other possible pathophysiological causes should be further actively explored. Our results may have practical implications for the on-going efforts to development of using estrogen, either alone or in combination with progestogen, to reduce the risk of screening detected cerebral aneurysms from rupture (11)(12)(13)(14). …”
Section: Discussionmentioning
confidence: 87%
“…Clinical trials show hormone replacement therapy (HRT) seems to be associated with a reduced risk for aneurysmal SAH (12,13). Experimental study also demonstrated a sex-specific hormonal factor may play a role in the pathogenesis of aneurysm formation and rupture (14,15). Because it is a relatively common cause of stroke in women under age 65 and because of its high morbidity and mortality, the excess of aneurysmal SAH in women remains a pressing question in stroke research.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that the female preponderance of intracranial aneurysms becomes significant only after the fourth or fifth decade, during the perimenopausal and postmenopausal periods. Moreover, estrogen has a protective effect against vascular injury [46] and hormone-replacement therapy has been shown to be a protective factor for subarachnoid hemorrhage [47].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%